A terapia fotodinâmica na quimiotaxia de neutrófilos e linfócitos T no tecido periodontal - Mernick, Ana Paula de Souza (2014)
Periodontitis is an infectious disease characterized by the destruction of the supporting tissues of the teeth and therefore the dental loss. Neutrophils are the first cells to arrive in periodontal inflammation and have as function phagocytosis and cytokine release. After a few days, the neutrophils are replaced by lymphocytes, which give the chronic nature of periodontitis. The established treatment for periodontitis is oral hygiene care, scaling and root planing, and in more advanced cases, there may be the need for systemic antibiotics. In order to reduce the prescription of antibiotics, it has been researched the use of photodynamic therapy (PDT) as antimicrobial intervention, with great results. The objective of this work is to verify if the PDT interferes with the chemotaxis of neutrophils and T lymphocytes into the periodontal tissue. For such, 05 patients who had undergone prior treatment with periodontal good oral hygiene and periodontal pockets with residual surgical indication were allocated. PDT was applied under the following parameters: methylene blue (50 µg/ml) was applied to the bottom of the periodontal pocket and after 5 minutes, via transmucosal, was irradiated with diode laser 660 nm, P = 100 mW, t = 90 s per point 9 J/point, energy density: 22 J/cm2, power density: 250 mW/cm2. One week after PDT, the surgical removal of the periodontal pockets was performed and the samples sent for routine histology and immunohistochemistry for detection of neutrophil and lymphocyte. The samples were photographed and positive cells counted with the aid of ImageJ software. The data were evaluated statistically and no significant difference between groups (Mann-Whitney p = 0.5). It was concluded that PDT did not interfere with the chemotaxis of neutrophils and T lymphocytes in the periodontal tissue after 7 days.